The importance of extensional strains in the analysis of reinforced concrete structures - Liebenberg, Algernon Charles (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2017)
The subject matter of the above-mentioned thesis has been sub-divided into four books, each of which represents a distinct contribution to knowledge although they together form a whole. The common theme of Books I, III and IV is the importance of extensional stresses and strains which are usually considered to be of secondary magnitude but which under certain conditions become of primary importance in the correct analysis of building structures. Book II is included as it formed the basis of the development of the theory in Book III. The order of arrangement corresponds approximately with the chronological development.